2013
DOI: 10.1007/s00436-013-3482-4
|View full text |Cite
|
Sign up to set email alerts
|

Gut transcriptome of replete adult female cattle ticks, Rhipicephalus (Boophilus) microplus, feeding upon a Babesia bovis-infected bovine host

Abstract: As it feeds upon cattle, Rhipicephalus (Boophilus) microplus is capable of transmitting a number of pathogenic organisms, including the apicomplexan hemoparasite Babesia bovis, a causative agent of bovine babesiosis. The R. microplus female gut transcriptome was studied for two cohorts: adult females feeding on a bovine host infected with B. bovis and adult females feeding on an uninfected bovine. RNA was purified and used to generate a subtracted cDNA library from B. bovis-infected female gut, and 4,077 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 58 publications
3
23
0
Order By: Relevance
“…Similar results were observed in the gut transcriptome of D. variabilis, for which the percentage of secreted transcripts among the genes expressed was small (ANDERSON et al, 2008). Fifty-three percentage of the transcripts differentially expressed in the gut transcriptome of R. microplus females were classified as intracellular and 18% as membranous (HEEKIN et al, 2013).…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Similar results were observed in the gut transcriptome of D. variabilis, for which the percentage of secreted transcripts among the genes expressed was small (ANDERSON et al, 2008). Fifty-three percentage of the transcripts differentially expressed in the gut transcriptome of R. microplus females were classified as intracellular and 18% as membranous (HEEKIN et al, 2013).…”
Section: Discussionsupporting
confidence: 69%
“…The classification from the automated analysis showed that the category of catalytic activity category was prevalent, thus indicating that many of the digestive tract transcripts were enzymes, such as oxidoreductases, transferases, hydrolases, lyases, isomerases and ligases. In the gut transcriptome of R. microplus, binding and catalytic activity was also identified as the most common functional types of activity (HEEKIN et al, 2013). The same results were observed by Xu et al (2016), who classified 47 and 42% of the transcripts of H. flava in the functional categories binding and catalytic activity, respectively.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations